Short term memory for tactile stimuli. - Gallace, A; Tan, H; Haggard, P; Spence, C (2008)
Research has shown that unreported information stored in rapidly decaying visual representations may be accessed more accurately using partial report than using full report procedures (e.g., [Sperling, G., 1960. The information available in brief visual presentations. Psychological Monographs, 74, 1-29.]). In the 3 experiments reported here, we investigated whether unreported information regarding the actual number of tactile stimuli presented in parallel across the body surface can be accessed using a partial report procedure. In Experiment 1, participants had to report the total number of stimuli in a tactile display composed of up to 6 stimuli presented across their body (numerosity task), or else to detect whether or not a tactile stimulus had previously been presented in a position indicated by a visual probe given at a variable delay after offset of a tactile display (i.e., partial report). The results showed that participants correctly reported up to 3 stimuli in the numerosity judgment task, but their performance was significantly better than chance when up to 5 stimuli were presented in the partial report task. This result shows that short-lasting tactile representations can be accessed using partial report procedures similar to those used previously in visual studies. Experiment 2 showed that the duration of these representations (or the time available to consciously access them) depends on the number of stimuli presented in the display (the greater the number of stimuli that are presented, the faster their representation decays). Finally, the results of a third experiment showed that the differences in performance between the numerosity judgment and partial report tasks could not be explained solely in terms of any difference in task difficulty.